An Overview of the Level of Anxiety N Children When Installing Infusions in the Emergency Department of the Islamic Hospital Purwokerto - Dicky Yudhistira Pradana Dicky; Noor Yunida Triana; Fauziah Hanum (PROMOTOR, 2024)
Hospitalization is a crisis condition for every child admitted to the hospital. Separation from parents often causes significant emotional changes in children, such as anxiety. In Central Java Province, child hospitalization is 4.1% of the total population. Anxiety is a vague worry characterized by feelings of uncertainty and helplessness. Anxiety in children can arise because of something new and has never been experienced before, insecurity and discomfort, a feeling of losing something they are used to, and something that feels painful. The purpose of this study was to determine the Anxiety of Children During Infusion Installation in the Emergency Department of Purwokerto Islamic Hospital. This study is a descriptive study with a cross sectional approach. The sample in this study were pediatric patients in the Emergency Room of Purwokerto Islamic Hospital, a total of 30 respondents using accidental sampling technique. Data analysis in this study was univariate analysis. The results showed that the anxiety level of children in the Emergency Department of Purwokerto Islamic Hospital when installing infusions experienced moderate anxiety as many as 16 children (53.3%). Future researchers are advised to research interventions that can reduce children's anxiety during infusion.